Pins Gene Table v2.0: An Online Genome Database of 37 Pythium insidiosum Strains for Gene Content Exploration and Phylogenomic Analysis - Weerayuth Kittichotirat; Preecha Patumcharoenpol; Thidarat Rujirawat; Sithichoke Tangphatsornruang; Chompoonek Yurayart; Theerapong Krajaejun (Journal of Fungi, 2024)
Unlike most pathogenic oomycetes, Pythium insidiosum infects humans and animals instead of plants. P. insidiosum has three clinically relevant genotypes/clades that cause a severe disease called pythiosis. To develop strategies for infection control, it is necessary to understand the biology and pathogenesis of this pathogen. Investigating the evolutionary mechanisms behind the host-specific adaptation is vital, and comparative genomic analysis can help with this. To facilitate genomic analysis, an online bioinformatics tool called P. insidiosum (Pins) Gene Table v2.0 was developed. This tool includes genomic data from 37 genetically diverse P. insidiosum strains and four related species. The database contains 732,686 genes, grouped into 80,061 unique clusters and further divided into core and variable categories at genus, species, and genotype levels. A high-resolution phylogenomic relationship among P. insidiosum strains and other oomycetes was projected through hierarchical clustering and core gene analyses. 3156 P. insidiosum-specific genes were shared among all genotypes and may be responsible for causing disease in humans and animals. After comparing these species-specific genes to the MvirDB database, 112 had significant matches with 66 known virulence proteins, some of which might be involved in vascular occlusion, which is a pathological feature of pythiosis. The correlation of genotypes, geographic origins, and affected hosts of P. insidiosum suggests that clade-I strains are more specific to animals, while clade-II/III strains are more specific to humans. The clade-specific genes might link to host preference. In summary, Pins Gene Table v2.0 is a comprehensive genome database accessible to users with minimal bioinformatics experience for the analysis of P. insidiosum genomes.